Understanding the Impact of Work from Home Arrangement on Psychological Empowerment - Prof. Dr. Poonam Vatharkar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Psychological empowerment can be understood as a sense of self control with respect to one’s work and active involvement with one’s work related role. It is manifested when employees feel that the work they do is personally meaningful to them, they have required competence to get the work done, they also have a degree of self-determination in taking work related decisions and their work has some impact on others and on the organizational as a whole. Psychological empowerment results in positive organizational and managerial outcomes. Today’s era is marked by tremendous changes in ways of work including the work from home arrangements. Because of the COVID-19 Pandemic situation, working from home arrangement is peremptory. The current study focuses on the working from home arrangements, personal life characteristics of individuals which might have an impact on psychological empowerment of employees. Gender differences, marital status, working hours, childcare responsibilities are expected to have impact on psychological empowerment of employees. T Test and Analysis of Variance (ANOVA) were used to test the hypothesis. The results of this study show that gender differences, marital status, childcare responsibility and working hours affect psychological empowerment of employees. The results also focus on need to reduce insecurity in the minds of remote working employees. The implications for the organizations and limitations of the study are also discussed.